Pengaruh Edukasi Anatomi Organ Reproduksi Wanita terhadap Pengetahuan Kesehatan Reproduksi Remaja Putri - Novita Sari, Nela; Maifita, Yesi (Pustaka Galeri Mandiri, 2026)
Adolescent girls require accurate reproductive health knowledge to understand pubertal changes, menstruation, self-care practices, and early signs of reproductive organ disorders. This study aimed to analyze the effect of female reproductive organ anatomy education on reproductive health knowledge among adolescent girls. The researchers applied a pre-experimental design using a one-group pretest-posttest approach at SMPN 7 Pariaman in May 2026. The study involved 20 adolescent girls selected through purposive sampling. The educational intervention combined anatomical presentations, labeled illustrations, reproductive organ models, and interactive discussions for 45 minutes. Knowledge was measured using a validated questionnaire consisting of 20 items. The difference in knowledge scores was analyzed using the Wilcoxon test. The mean knowledge score increased from 62 in the pretest to 84 in the posttest, with a mean difference of 22 points. Statistical analysis showed a significant improvement in knowledge (p = 0.01). Education integrating anatomical concepts with practical reproductive health messages can strengthen conceptual understanding and reduce adolescents’ misconceptions. Schools and nursing professionals should provide reproductive health education regularly through interactive, age-appropriate approaches that consider cultural contexts.